In Vivo Visualization of Charcot-Bouchard Aneurysms on Lenticulostriate Arteries Using 7T MRI - Jiaerken, Yeerfan; Benjamin, Philip; Rodgers, Christopher T.; Cai, Lupei; Nannoni, Stefania; MacKinnon, Andrew D.; Markus, Hugh S. (American journal of neuroradiology : AJNR, 2025)
Charcot-Bouchard aneurysms (CBAs) are tiny aneurysms arising from small perforating arteries. Despite the potentially catastrophic consequences of rupture of these aneurysms, the existence and prevalence of CBAs are controversial. The literature in this area is sparse with most previous studies based on radiologic case reports of single hemorrhage or histopathologic analysis. 7T MRI provides higher spatial resolution than 3T MRI, which enables imaging of the small perforating arteries. We determined whether CBAs could be detected in vivo by using 7T MRI. Ninety-four patients with ischemic stroke collected in the Cambridge 7T Cerebral Small Vessel Disease study prospective cohort were retrospectively included; 75 of them had lacunar infarcts due to presumed small vessel disease, and 19 had nonlacunar infarcts due to presumed cardioembolism or large artery disease. Contrast-enhanced 3D time-of-flight angiography (MRA) and structural sequences were performed by 7T MRI. Two neuroradiologists independently reviewed the MR scans to identify aneurysms on the lenticulostriate arteries (LSA) bilaterally. In 4 of the 94 subjects, CBAs were detected in the LSA; of these, 3 had a single CBA, and 1 had 2. The diameter of the parent vessel ranged from 0.26 mm-0.37 mm and the maximum diameter of the CBA ranged from 0.73 mm-1.39 mm. Use of 3D images allowed differentiation of looped vessels, which could mimic aneurysms on 2D images, from true CBA. We have demonstrated that 7T MRI can detect CBAs in vivo in humans. This technique could allow further longitudinal studies to determine the true prevalence and prognostic significance of CBAs.